2005
DOI: 10.1097/01.psy.0000188402.95398.c0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Attributions, Distress, and Health Practices Among Gynecologic Cancer Survivors

Abstract: Results suggest that stronger attributions are associated with greater distress, but engaging in behavior believed to be important in preventing cancer or recurrence may ameliorate this distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
87
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 47 publications
(61 reference statements)
13
87
1
Order By: Relevance
“…In keeping with other studies [6][7][8][9][10]12], and irrespective of whether the response was prompted or not, ''Stress'' was found to be the most frequently stated contributing factor among cancer patients (Table 2). Some research indicates that stressful experiences have adverse effects on immune response, which can lead to detrimental medical outcomes in situations where disease is normally mediated or resisted by the immune system [23].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In keeping with other studies [6][7][8][9][10]12], and irrespective of whether the response was prompted or not, ''Stress'' was found to be the most frequently stated contributing factor among cancer patients (Table 2). Some research indicates that stressful experiences have adverse effects on immune response, which can lead to detrimental medical outcomes in situations where disease is normally mediated or resisted by the immune system [23].…”
Section: Discussionsupporting
confidence: 75%
“…Other papers on the topic from the USA and one from Israel reported similar findings [7][8][9][10]. These had relatively small sample sizes ranging between 60 and 378 participants, and there was a lack of congruency in the definitions and detail of the categories of causes used across these studies.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…An insignificant but relatively consistent inverse correlation pattern was observed between other breast cancer risk factors and the score on the CES-D as well; the attributions to five out of nine evaluated breast cancer risk factors showed an inverse correlation, indicating better psychological adjustment to the illness. The finding suggests that causal attributions to some breast cancer risk factors are likely to help patients adjust psychologically to the illness, although it has frequently been indicated in previous studies that forming causal attributions, mostly to non-risk factors, was associated with worsening psychological adjustment to the illness [6,7,9,33]. Similar to the results from a current study, those from a recent study about health behavior among breast cancer patients indicated that patients who attributed their illness to certain breast cancer risk factors later modified their behaviors appropriately in response to the attributions, indicating better behavioral adjustment to the illness [26].…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have indicated that forming causal attributions or selfblame decreases psychological adjustment to the illness among breast and cervical cancer patients [6,7,9,17,33]. Other studies have reported that none of the attributions formed among breast cancer patients was associated with depression or overall adjustment to the illness [19,35] We hypothesized that causal attributions to each risk factor have a different influence on an individual's psychological adjustment to the illness.…”
Section: Introductionmentioning
confidence: 98%